Practical Problematics of Political Communication : Peculiarities of the President D. Grybauskaitė's Rhetoric (Parliamentary Studies, 2010)
The article is intended to analyze the practical problems of political communication, to wit the peculiarities and importance of rhetoric used by political leaders. The paper provides a review on the President D. Grybauskaitė's rhetoric, itself an interesting and problematic case of Lithuanian political rhetoric. Further, a synopsis of the rhetoric of political leaders and presidents is set out, along with the role of rhetoric per se in the processes of political communication.
Keywords: political rhetoric; rhetoric of a leader